Un tournant technique des sciences (sociales) du droit ? - Frédéric Audren (Clio@Themis)
After explaining how the two translated texts articulate law and geography, this article emphasizes that they take "legal technicalities" seriously. After reviewing the invisibility of legal knowledge and techniques in many social science studies, the article argues, as do these two texts, that research should focus more systematically on legal activity and knowledge. The study of the practical organization of the work of legal actors, their reasoning, their use of categories and concepts in context, lay the foundations for a social science of law. By focusing on this "work of law", on law as a real and empirically observable performance, as a concrete and situated activity, the dialogue between jurists and social sciences could be effectively and durably renewed.